The phenomenon of traditional philanthropy through the voluntary sector in shaping community identity - Kurniati, Pat; Sapriya, Sapriya; Darmawan, Cecep; Rolando P., Quinones Jr; Putra, Haris Maiza (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
The role of the state is needed to suppress illegal philanthropic practices, how the state can make Pancasila a "civic religion". Pancasila as the basis and pillar of society's civility as well as the "social glue" where sanctified spaces and symbols become markers of social identification that connect individuals in a common bond. The purpose of this research is to discuss the phenomenon of traditional philanthropy through the voluntary sector in shaping community identity. This research uses qualitative research methods, with the research design using a descriptive approach research design. In this study, the author conducts library research, then describes the phenomenon of traditional philanthropy through the voluntary sector in shaping community identity. The results show that philanthropy develops along with the development of human life itself. Voluntary sector refers to organizations whose primary goal is to create social impact rather than profit. This is often called the third sector, civil society or the nonprofit sector. The value of social justice and community welfare, especially in developing community identity empowerment, such as health services for poor families, economic empowerment, scholarships, job training, capital provision for middle to lower traders and others aimed at empowering community identity through philanthropy.